β-arrestin2 functions as a key regulator in the sympathetic-triggered immunodepression after stroke - Huan Wang; Qi-Wen Deng; Ai-Ni Peng; Fang-Lan Xing; Lei Zuo; Shuo Li; Zheng-Tian Gu; Fu-Ling Yan (Journal of Neuroinflammation, 2018)
Abstract Background Stroke-induced immunodeficiency syndrome (SIDS) is regarded as a protective mechanism for secondary inflammatory injury as well as a contributor to infection complications. Although stroke-induced hyperactivation of the sympathetic system is proved to facilitate SIDS, the involved endogenous factors and pathways are largely elusive. In this study, we aim to investigate the function of beta-arrestin-2 (ARRB2) in the sympathetic-mediated SIDS. Methods Splenic ARRB2 expression and the sympathetic system activity were detected after establishing transient models of middle cerebral artery occlusion (MCAO). In addition, a correlation between ARRB2 expression and the sympathetic system activity was analyzed using a linear correlation analysis. Any SIDS reflected in monocyte dysfunction was investigated by measuring inflammatory cytokine secretion and neurological deficit scores and infarct volume were tested to assess neurological outcome. Further, ARRB2 expression in the monocytes was knocked down in vitro by siRNAs. Following the stimulation of noradrenaline and lipopolysaccharide, cytokine secretion and the nuclear factor-κB (NF-κB) pathway were evaluated to gain insight into the mechanisms related to the contribution of ARRB2 to adrenergic-induced monocyte dysfunction. Results Splenic ARRB2 expression was significantly increased after stroke and also showed a significant positive correlation with the sympathetic system activity. Stroke-induced monocyte dysfunction resulted in an increase of the interleukin-10 (IL-10) level as well as a decrease of the interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) levels. Also, blockade of adrenergic-activity significantly reversed these cytokine levels, and blockade of adrenergic-activity improved stroke-induced neurological results. However, the improved neurological results had no significant correlation with ARRB2 expression. Furthermore, the in vitro results showed that the deficiency of ARRB2 dramatically repealed adrenergic-induced monocyte dysfunction and the inhibition of NF-κB signaling phosphorylation activity. Conclusions ARRB2 is implicated in the sympathetic-triggered SIDS, in particular, monocyte dysfunction after stroke. Accordingly, ARRB2 may be a promising therapeutic target for the immunological management of stroke in a clinic.